When Permissioned Blockchains Deliver More Decentralization Than Permissionless. - Bakos, Yannis; Halaburda, Hanna; Mueller-Bloch, Christoph (Communications of the ACM, 2021)
The article discussed the use of what are referred to as permissioned blockchains in decentralizing computer systems governance. It examines the differences between open and permissioned access and argues that open access could result in centralized control.